Literasi Digital, Budaya Membaca, dan Kesiapan Guru Sekolah Dasar terhadap Pembelajaran AI dan Coding: Studi Perbandingan Indonesia dan Malaysia. - Desi Eka Pratiwi; Nurul Agustin; Suprihatien Suprihatien; Nataria Wahyuning Subayani (EduStream: Jurnal Pendidikan Dasar, 2026)
The transformation of twenty-first century education requires elementary school teachers to be well-prepared to integrate artificial intelligence (AI) and coding technologies into classroom practice. However, disparities in digital literacy and reading culture may influence teachers’ readiness across different national contexts. This study aims to examine the role of digital literacy and reading culture in shaping elementary school teachers’ readiness for AI- and coding-based learning through a comparative analysis of Indonesia and Malaysia. This study employed a qualitative approach with a comparative study design, combining a systematic literature review and in-depth interviews with expert informants. Secondary data were obtained from peer-reviewed journal articles, educational policy documents, ministry reports, and verified mass media sources. The findings reveal that digital literacy significantly enhances teachers’ capacity to design, implement, and evaluate AI- and coding-based instructional practices, while a strong reading culture supports teachers’ adaptability in responding to technological innovations. From a comparative perspective, Malaysia demonstrates a higher level of teacher readiness, supported by integrated digital literacy policies and continuous professional development programs. In contrast, Indonesia faces challenges related to digital infrastructure and unequal access to teacher training. These findings imply the need to strengthen digital literacy initiatives, foster technology-oriented reading cultures, and enhance cross-national policy collaboration to support teachers in implementing AI- and coding-based learning effectively. This study contributes to both theoretical and practical perspectives for policymakers and primary education practitioners in addressing the challenges of educational digital transformation.